Changes in cerebral glucose metabolism after acupuncture at KI3 in spontaneously hypertensive rats: a positron emission tomography study. Issue 2 (April 2019) - Li, Jing; Peng, Chong; Lai, Dongjian; He, Kejie; Wang, Yumei; Zhang, Gaochuan; Wu, Yuwen; Nie, Binbin; Shan, Baoci; Tang, Chunzhi; Lai, Xinsheng
Objective: The aim of this study was to explore the effect of acupuncture stimulation at KI3 on brain glucose metabolism in spontaneously hypertensive rats (SHRs). Methods: Brain glucose metabolism in SHRs after acupuncture stimulation at KI3 was detected using 18F-2-fluorodeoxy-D-glucose positron emission tomography (18F-FDG-PET). SHRs were randomly divided into three groups: no treatment (SHR group); acupuncture at KI3 (KI3 group); and sham acupuncture (Sham group). Wistar Kyoto (WKY) rats were used as a normal blood pressure (BP) control group. Rats were subjected to 10 min of acupuncture once a day for 7 days. BP and positron emission tomography–computed tomography (PET-CT) were measured after the first acupuncture session and after 7 days of treatment. Results: The results showed that BP was lower in the KI3 group than in the SHR group, both 30–60 min after the first acupuncture session and 24–48 h after the 7-day treatment. Compared with the WKY group, the SHR group had lower glucose metabolism in the motor cortex, sensory cortex, basal ganglia, corpus callosum, caudate putamen, and visual cortex. Compared with the untreated/sham-treated SHR control groups, cerebral glucose metabolism was lower in the medulla oblongata, thalamus, dorsal thalamus, orbital cortex, and hypothalamus after acupuncture at KI3, while it was higher in the olfactory cortex and inferior phrenic muscle. Conclusion: Our results show that, in SHRs, needling at KI3 reduces high BP, most likely by altering the activation of cerebral regions.